Effect on oxides on surface topography and thermal contact resistance - Mian, M. N. (Cranfield University, 1979)
The effect of oxides on the topographies of various random engineering surfaces and steady-state thermal contact resistances between oxidefree and oxidized metallic surfaces in contact in high vacua have been investigated. The results of many previous investigations indicated that such problems cannot be dealt with without a detailed study of the surface topographies, resulting in accurate surface characterisation. The distributions of the real micro-contact zones and heat transfer phenomena across interfaces could 'then be predicted. Cylindrical specimens normally mild steel EN3B and commercially pure copper of nominal area 4.908 x 10-4 m2 were oxidized under controlled environmental conditions and subsequently pressed into contact at their flat faces. The oxide film thickness measurements were taken using a high resolution Stereoscan electron microscope. Surface topographies were quantified before and after oxidation to determine the effects of oxide films upon their topological characteristics. Following a detailed analysis, two theories concerning the problem of predicting thermal contact resistances of oxidized joints having Gaussian distribution of surface heights have been developed. The developed theories establish the surface parameters measured to design a predictable thermal joint and apply for thin films of the order of naturally occurring oxides. From a statistical analysis of the experimental measurements for freshly-assembled contacts, an empirical expression (R = 66.0 p-0.945 a-0.128 X0.0346) has been established relating the loading pressure, mean roughness of'the contacting surfaces and oxide film thickness to the thermal resistance of the contacts in high vacua. Finally a method of producing joints with low thermal contact resistance (and vice versa) is suggested.